A protecção social das pessoas idosas na Carta Social Europeia revista, no Código Europeu da Segurança Social e no Direito Português - Faria, Paula Ribeiro de (2017)
This article tackles the importance of the European Social Charter in the defense of the social rights of older people in the context of the major social and economic crisis that is affecting Europe. In a Europe that is dominated by competitiveness concerns and economic interests, the intervention of the European Committee of Social Rights and the European Social Charter, play an essential role on the maintenance of the social rights of the European citizens, especially of the most disadvantaged population groups. The protection afforded by the European Social Charter and the national law to the rights of older people is identified, as well as the way our country has been trying to respond to the demands placed upon him by the European Social Charter in this area.